Antimicrobial, antibiofilm, cytotoxicity, and substantivity of aged garlic extract against oral bacteria: an in-vitro study - Meghana Sunil; Bhaskar Kurangi; Suneel Dodamani; Marwa Khalil; Aditi Chopra (BMC Complementary Medicine and Therapies)
Abstract Background Garlic (Allium sativum L.) is a powerful antimicrobial, antioxidant, and anti-inflammatory agent. Aged garlic has more antioxidant and antimicrobial properties compared to fresh garlic. Garlic has been used for the treatment of many oral and periodontal diseases. However, the efficacy of aged garlic extract (AGE) against periodontal pathogens has never been explored. Hence, this in vitro study aims to assess the antimicrobial, antibiofilm, substantivity, and cytotoxic properties of AGE against key periodontal pathogens and oral tissues. Methods The antimicrobial properties of the AGE were evaluated by assessing the minimal bactericidal concentration (MBC) and minimal inhibitory concentration (MIC) against Actinomyces viscosus, Streptococcus salivarius, Fusobacterium nucleatum, Prevotella intermedia, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Tannerella forsythia compared to doxycycline and chlorhexidine using the serial dilution method. The antibiofilm properties of AGE were checked for A. actinomycetemcomitans, and F. nucleatum was checked using the standard crystal violet staining assay. The cytocompatibility was checked against human-derived gingival and periodontal fibroblasts and modified oral keratinocytes using 3-4-5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide (MTT) assay. The substantivity of the extract was checked against chlorhexidine on the dentin surface from extracted tooth samples using an ultraviolet spectrophotometer. Results The growth of A. viscosus, F. nucleatum, and S. salivarius was inhibited by AGE at 50 µg/ml. At 25 µg/ml, P. gingivalis and A. actinomycetemcomitans were inhibited. P. intermedia growth required a higher concentration of 100 µg/ml. At 25 µg/ml and 100 µg/ml, AGE showed bactericidal activity against A. viscosus and P. intermedia, respectively. The anti-biofilm assay showed that the percentage inhibition was 37.99% for F. nucleatum and 2.52% for A. actinomycetemcomitans. The cell viability of gingival fibroblasts (90%) and modified human keratinocytes (80%) was maintained by AGE at concentrations of 2.5 mg/ml and 5 mg/ml, respectively. The mean difference in substantivity for chlorhexidine and AGE at one minute was statistically significant (p = 0.0112). Conclusion AGE was effective in inhibiting the growth of periodontal pathogens. However, its antimicrobial effects were not statistically significant when compared to doxycycline. AGE is biocompatible with gingival and periodontal ligament fibroblasts and has good substantivity to the dentin surface.